2022
DOI: 10.2147/rmhp.s346998
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Perception, and Practice, and Attitudes Towards Self-Medication Among Undergraduate Medical Students of Najran University, Saudi Arabia: A Cross-Sectional Study

Abstract: Background: Self-medication (SM) is a customary practice around the globe. Appropriate SM comes with many advantages, yet irrational SM is a concern and could lead to adverse drug events and poor health outcomes. Methods: This college-based cross-sectional study was carried out from January to March 2021 among Najran University undergraduate medical students to investigate the prevalence and practice of, and attitudes towards SM. Data were collected using a bilingual self-administered online questionnaire, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 26 publications
4
26
0
Order By: Relevance
“…The principal findings of the present study revealed that 51.6% of the students normally used OTC medications during exam time. Our results demonstrated a lowered percentage of comprehension when compared with the findings of earlier studies performed in other Saudi Arabian universities [ 17 , 18 ]. These studies indicated that overall, the prevalence of self-medication among female students was 98.2% in Hail, Saudi Arabia, and the most often cited medical reasons that induced such self-medication practices were headaches (92.85%); after that came cough (37.5%), colic (31.9%), and influenza (30.3%) [ 13 ].…”
Section: Discussionsupporting
confidence: 52%
“…The principal findings of the present study revealed that 51.6% of the students normally used OTC medications during exam time. Our results demonstrated a lowered percentage of comprehension when compared with the findings of earlier studies performed in other Saudi Arabian universities [ 17 , 18 ]. These studies indicated that overall, the prevalence of self-medication among female students was 98.2% in Hail, Saudi Arabia, and the most often cited medical reasons that induced such self-medication practices were headaches (92.85%); after that came cough (37.5%), colic (31.9%), and influenza (30.3%) [ 13 ].…”
Section: Discussionsupporting
confidence: 52%
“…This result is consistent with other similar studies of health science students in Ethiopian higher educational institutions such as Arsi University, 33 University of Gondar, 37,68 Private Health Science Colleges in Gondar, 69 and Mekelle University. 70 There are also confirming reports from Bahrain, 22 Eritrea, 39 Saudi Arabia, 71 and India 30,53,62 on the frequently used SM groups and perceived disease conditions. Similarly, analgesics and antibiotics were the two foremost self-medicated drugs in Nigerian students, 72 whereas non-steroidal analgesic, anti-inflammatory, and antipyretic drugs were the most frequently used OTC drugs for self-treating fever and headaches in Nepal.…”
Section: Attitude Towards Self-medication and Associated Factorsmentioning
confidence: 56%
“…According to this survey, SM use was reported to be practiced by 58.1% of the participants. Studies including university students from Egypt have found a similar incidence (62.9%), 10 Najran University in Saudi Arabia (60%), 18 University of Gondar (52.4%), 7 Mbarara University of Science and Technology in Uganda (63.5%) 16 among medical and…”
Section: Discussionmentioning
confidence: 83%